Disclosure of Islamic Social Reporting (ISR) through leverage, profitability and company size - Rahmawati.S; Andi Sulfati; Asbi Amin (www.amertainstitute.com, 2024)
The goal of this research is to find out how Islamic banks that were registered with the Financial Services Authority (OJK) between 2020 and 2023 disclosed their Islamic social reporting (ISR), taking into account factors including leverage, profitability, and company size. Gathering information using a purposive sample method based on secondary sources such as financial and sustainability reports found on each bank's website. There were thirteen observations in the population and thirty-six in the sample, all of which pertain to Islamic banks that were registered with the Financial Services Authority (OJK) in 2020 and 2023. Multiple linear regression and hypothesis testing are the tools of choice for this investigation. This study found that Islamic Social Reporting (ISR) Disclosure is positively affected by leverage, but unaffected by profitability. Another favorable effect of company size on ISR Disclosure was shown to be statistically significant.